Psycho-social and psychiatric co-morbidity among children with poisoning - Ali Lodhi, Liaqat; Yousuf Mir, Naseer; Wani, Khurshid Ahmad; Akhter, Samina (International Journal of Contemporary Pediatrics, 2022)
Background: The poisoning in children results from exposures to toxic agents that may lead to harmful effects based on the reaction of the body to these agents. Poisoning can be accidental or suicidal in intent. To assess any psycho-social factor that leads to poisoning and to determine any underlying psychiatric co-morbidity among children with acute poisoning. Methods: A hospital-based prospective observational study conducted in postgraduate department of pediatrics, G. B. Pant children’s hospital an associated hospital of government medical college Srinagar Jammu and Kashmir India. This study was conducted over 2 years with effect from November 2019 to November 2021. Psychiatric co-morbidity was determined by using the MINI- KID scale. Results: In our study, 572 cases with poisoning were studied over two years; the mean age of childhood poisoning was 3.8 years. The majority of the poisoning cases were accidental, with male to female ratio of 1.6:1. Most of the cases were seen in lower-middle-class families (65.7%). Organophosphorus was the most common agent involved. Oral ingestion was the predominant route of poisoning. A total of 46 subjects had a psychiatric diagnosis as assessed by MINI-KID. Among which, 34.7% of the subjects had the diagnosis of panic disorder, followed by depressive episodes (MDD) amounting to 26%, and ADHD in 13%. A total of 53 were having underlying psychosocial factors. Adolescent self-poisoning is commonly associated with underlying psychiatric illness. Conclusions: The underlying psychosocial and psychiatric disorders need proper identification and management.